2021
DOI: 10.1186/s12884-021-04047-2
|View full text |Cite
|
Sign up to set email alerts
|

Tocolysis in the management of preterm prelabor rupture of membranes at 22–33 weeks of gestation: study protocol for a multicenter, double-blind, randomized controlled trial comparing nifedipine with placebo (TOCOPROM)

Abstract: Background Preterm prelabor rupture of membranes (PPROM) before 34 weeks of gestation complicates 1% of pregnancies and accounts for one-third of preterm births. International guidelines recommend expectant management, along with antenatal steroids before 34 weeks and antibiotics. Up-to-date evidence about the risks and benefits of administering tocolysis after PPROM, however, is lacking. In theory, reducing uterine contractility could delay delivery and reduce the risks of prematurity and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
(104 reference statements)
0
4
0
1
Order By: Relevance
“…Statistically, most cases of PROM occur at a GA of 25-32 weeks 48 , and approximately 60% of premature deliveries occur within the rst week after PROM 49 ; dysontogenetic newborns from these cases are extremely di cult to keep alive. A study conducted by the Lancet indicated that the survival rate of extremely preterm infants, de ned as being delivered before 28 weeks, was only 17%-41% and was accompanied by a disability rate of approximately 30% 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Statistically, most cases of PROM occur at a GA of 25-32 weeks 48 , and approximately 60% of premature deliveries occur within the rst week after PROM 49 ; dysontogenetic newborns from these cases are extremely di cult to keep alive. A study conducted by the Lancet indicated that the survival rate of extremely preterm infants, de ned as being delivered before 28 weeks, was only 17%-41% and was accompanied by a disability rate of approximately 30% 50 .…”
Section: Discussionmentioning
confidence: 99%
“…This illustrates the need for clinical practice guidelines that reflect rural and remote practice, for remote emergency clinicians (11). A clinical trial is currently investigating the risks and benefits of administering tocolysis after preterm prelabour rupture of membranes, with important implications for rural and remote maternity services (36).…”
Section: Discussionmentioning
confidence: 99%
“…To emphasize, preterm birth is still a challenge to researchers studying its basic mechanisms, and though there have been some recent headways into its molecular pathways and prediction models [ 15 ], the question of when to start tocolytic therapy and for how long remains a common but difficult decision for clinicians. Currently, it is generally recommended that tocolysis be limited to the occurrence of preterm labor between the gestational ages (GA) of 24 weeks and 30 weeks or to those over 30 weeks of GA accompanied with cervical length <15 mm or 20 mm [ 4 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The most acceptable strategy is acute tocolysis or 48 h of tocolytic agent use for steroid and magnesium sulphate (MgSO4) administration, as well as to gain time for maternal–fetal transfer [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%